Role of VIA in Cervical Cancer Screening in Low-Resource Countries. - Nahar, KN; Nessa, A; Shamim, S; Nasrin, B; Hossain, F; Begum, N (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):528-535 The abstract of this article is available on the PubMed website